Size effect on the compressive fatigue of fibre-reinforced concrete. (7th March 2022) - Ortega, J.J.; Ruiz, G.; Poveda, E.; González, D.C.; Tarifa, M.; Zhang, X.X.; Yu, R.C.; Vicente, M.Á.; de la Rosa, Á.; Garijo, L.
Abstract: The size effect on the compressive fatigue behaviour of fibre-reinforced concrete is herein studied by testing cubes of 40 mm, 80 mm and 150 mm in edge length. Even though the compressive strength resulted the same in the three cases due to the ductility of the material in this range of sizes, the size effect was evident on the fatigue response of the 40-mm specimens, which reached numbers of cycles up to three orders of magnitude higher than expected. Furthermore, the mean residual strength of run-out specimens of this size increased by 42% due to the cyclic loads. Regarding the fatigue creep of the material, the logarithms of the secondary strain rate and the number of cycles to failure presented a linear relationship that is size-independent and can predict the fatigue life of run-out specimens. Meanwhile, the strain upon failure decreased with the increase of size although the crack patterns were still similar. Highlights: Increased fatigue life for smaller cubic specimen sizes of fibre-reinforced concrete. Constant compressive strength under the size of 150 mm due to the effect of fibres. Mean increment of a 42% in the post-fatigue compressive strength of run-out specimens. Size-independent relationship between the secondary strain rate and fatigue life. Decrease of fatigue failure strain for larger sizes.